Manfaat Internet Sebagai Sumber Belajar dalam Meningkatkan Kualitas Pendidikan Digital - Febry Andhara Zhahirah; Dona Viola (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid expansion of internet access has fundamentally altered how learners engage with educational content, offering unprecedented opportunities for knowledge acquisition beyond the confines of traditional classrooms. This study examines the multifaceted benefits of the internet as a learning resource, focusing on four principal dimensions: unlimited accessibility to educational materials, the diversity and richness of online learning content, personalization and autonomous learning, and cost-time efficiency. Employing a qualitative approach through systematic literature review, this research synthesizes findings from peer-reviewed journals, institutional reports, and empirical studies published between 2020 and 2025. The analysis reveals that the internet has effectively dismantled geographical and temporal barriers that once restricted educational access, particularly benefiting learners in remote and underserved regions. The sheer volume and variety of digital learning resources spanning open educational resources (OER), massive open online courses (MOOCs), digital libraries, and multimedia platforms afford learners the ability to construct highly personalized learning pathways aligned with individual needs, pace, and learning styles. Furthermore, internet-based education substantially reduces both direct costs, such as tuition and textbook expenses, and indirect costs, including commuting time. However, persistent challenges including the digital divide, information quality concerns, and the risk of over-reliance on passive consumption must be addressed to maximize the transformative potential of the internet in education. This study contributes to the growing body of literature on digital pedagogy and offers implications for educators, policymakers, and educational institutions seeking to optimize internet-based learning environments.